Applying Lean-Six-Sigma Methodology in radiotherapy: Lessons learned by the breast daily repositioning case. Issue 2 (May 2018) - Mancosu, Pietro; Nicolini, Giorgia; Goretti, Giulia; De Rose, Fiorenza; Franceschini, Davide; Ferrari, Chiara; Reggiori, Giacomo; Tomatis, Stefano; Scorsetti, Marta
Abstract: Background & purpose: Lean Six Sigma Methodology (LSSM) was introduced in industry to provide near-perfect services to large processes, by reducing improbable occurrence. LSSM has been applied to redesign the 2D-2D breast repositioning process (Lean) by the retrospective analysis of the database (Six Sigma). Materials & methods: Breast patients with daily 2D-2D matching before RT were considered. The five DMAIC (define, measure, analyze, improve, and control) LSSM steps were applied. The process was retrospectively measured over 30 months (7/2014–12/2016) by querying the RT Record&Verify database. Two Lean instruments (Poka-Yoke and Visual Management) were considered for advancing the process. The new procedure was checked over 6 months (1–6/2017). Results: 14, 931 consecutive shifts from 1342 patients were analyzed. Only 0.8% of patients presented median shifts >1 cm. The major observed discrepancy was the monthly percentage of fractions with almost zero shifts (AZS = 13.2% ± 6.1%). Ishikawa fishbone diagram helped in defining the main discrepancy con-causes. Procedure harmonization involving a multidisciplinary team to increase confidence in matching procedure was defined. AZS was reduced to 4.8% ± 0.6%. Furthermore, distribution symmetry improvement (Skewness moved from 1.4 to 1.1) and outlier reduction, verified by Kurtosis diminution, demonstrated a better "normalization" of the procedure after the LSSM application. Conclusions: LSSM was implemented in a RT department, allowing to redesign the breast repositioning matching procedure.